2020
DOI: 10.21203/rs.3.rs-26171/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipidomics Profiling of Skin Surface Lipids in Senile Pruritus

Abstract: Background: Senile pruritus is common, yet its etiology remains unknown. We examined the lipidomics profiles of skin surface lipids (SSL) in the elderly to better understand potential causes for senile pruritus. Methods:Transepidermal water loss (TEWL) was used to assess skin barrier function. Ameliorated Kawashima itch scale were used to measure the pruritus score. Liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) and multivariate data analysis were used to investigate SSL alternations. R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several studies have shown that wilt, senescence and drop of petals were caused by an increasing activity by endogenous ethylene, deterioration of cell wall components and an increasing activity of destroyed enzymes (Van Doorn, 2002;Wagstaff et al, 2003;Lerslerwong et al, 2009). A decrease in endogenous plant growth regulators could enhance the process of wilt and senescence (Lukaszewska et al, 1994: Ma et al, 2005. Therefore, an exogenous supply of these regulators could improve quality and flowering time in several ornamental plants (Saffari et al, 2004;Hoeberichts et al, 2007;Jiang et al, 2010;Sardoei, 2014;Mondal and Sarkar, 2018).…”
Section: Effect Of Several Plant Growth Regulators On Characteristics...mentioning
confidence: 99%
“…Several studies have shown that wilt, senescence and drop of petals were caused by an increasing activity by endogenous ethylene, deterioration of cell wall components and an increasing activity of destroyed enzymes (Van Doorn, 2002;Wagstaff et al, 2003;Lerslerwong et al, 2009). A decrease in endogenous plant growth regulators could enhance the process of wilt and senescence (Lukaszewska et al, 1994: Ma et al, 2005. Therefore, an exogenous supply of these regulators could improve quality and flowering time in several ornamental plants (Saffari et al, 2004;Hoeberichts et al, 2007;Jiang et al, 2010;Sardoei, 2014;Mondal and Sarkar, 2018).…”
Section: Effect Of Several Plant Growth Regulators On Characteristics...mentioning
confidence: 99%
“…Previous studies reported that the increased TEWL and decreased hydration content were associated with skin xerosis [12]. Skin surface lipids (SSLs) are a mixture of sebaceous gland lipids and intercellular lipids located in the outer layer of epidermal cells [13]. SSLs maintain skin barrier function, protect skin moisture content, and help regulate skin cell proliferation and apoptosis, cellular immunity, and in ammation.…”
Section: Introductionmentioning
confidence: 99%